AB0178 Elevated serum igg4 correlates with disease activity in patients with rheumatoid arthritis. (23rd January 2014) - Chen, L.-F.; Luo, L.; Mo, Y.-Q.; Zheng, D.-H.; Ma, J.-D.; Dai, L.
Abstract : Background: Elevated serum IgG4 is one of the characteristics of IgG4-related diseases and it has also been reported in some patients with rheumatoid arthritis (RA). However, the significance of elevated serum IgG4 in RA remains elusive. Objectives: To explore the correlation of serum IgG4 with disease activity measures in RA. Methods: Serum IgG and IgG4 levels from 129 Chinese RA patients were detected by immunonephelometry with BN ProSpec System. Patients were divided into hyper-IgG4 group (n=57) and normal-IgG4 group (n=72) according to the upper limit of normal serum IgG4 (135mg/dL). Furthermore, patients were divided into normal-IgG4/IgG group (≤8%, n=66) and hyper-IgG4/IgG group (>8%, n=63). Kruskal-Wallis one way analysis of variance on ranks and Spearman's rank correlation test were used. Results: (1) Among 129 RA patients, 75 (58%) were female, median age was 55 years (interquartile range (IQR) 42~61) and median disease duration was 36 months (IQR 24~96). Medians of serum IgG4, IgG and IgG4/IgG radio were 1.14g/L (IQR 0.57~2.04), 14.5g/L (IQR 11.8~17.3) and 8.0% (IQR 3.8%~14.6%), respectively. (2) Serum IgG4 and IgG4/IgG ratio of male patients were significantly higher than those of female (χ 2 =6.128, P =0.013 and χ 2 =9.898, P =0.002, respectively). (3) CRP, ESR, Patient Global Assessment of Disease Activity (PtGA), Provider Global Assessment of Disease Activity (PrGA) in hyper-IgG4 group were significantly higher than those in normal-IgG4 group (CRP: χ2=5.595, P =0.018; ESR: χ2=6.392, P =0.011; PtGA: χ2=9.646, P =0.002; PrGA: χ2=9.625, P =0.002; RF: χ2=11.317, P =0.001). (4) CRP, ESR, PtGA, PrGA, RF in hyper- IgG4/IgG group were significantly higher than those in normal-IgG4/IgG group (CRP: χ 2 =8.723, P =0.003; ESR: χ 2 =5.959, P =0.015; PtGA: χ 2 =7.987, P =0.005; PrGA: χ 2 =7.908, P =0.005; RF: χ 2 =9.468, P =0.002). (5) Serum IgG4 and IgG4/IgG ratio showed significant difference among disease activity groups according to CDAI and SDAI (all P <0.05). Multiple comparison indicated that serum IgG4 in high disease activity group was significantly higher than those in low disease activity group (CDAI: χ 2 =7.646, P =0.006, SDAI: χ 2 =8.017, P =0.005). No significant difference was found among different disease activity groups according to DAS28-CRP or PAS ( P >0.05). (6) There was significant correlation of serum IgG4 with 28-joint counts of tenderness (r=0.194, P =0.027), CRP (r=0.306, P <0.001), ESR (r=0.345, P <0.001), morning stiffness (r=0.255, P =0.006), RF (r=0.338, P <0.001), DAS28(4)-CRP (r=0.213, P =0.033), SDAI (r=0.203, P =0.042) and PAS (r=0.263, P =0.014). IgG4/IgG ratio significantly correlated with CRP (r=0.269, P =0.002), ESR (r=0.237, P =0.007), morning stiffness (r=0.185, P =0.048), RF (r=0.323, P <0.001) and PAS (r=0.213, P =0.049). Conclusions: Our results showed significant correlation of elevated serum IgG4 and IgG4/IgG ratio with disease activity measures in RA, suggesting that serum IgG4 and IgG4/IgG ratio maybe useful indicators of disease activity. Acknowledgements: This work was supported by the Chinese National Natural Science Research Grant (grant no. 30972742 and 81001334), the Natural Science Research Grant of Guangdong Province, China (grant no. 9151008901000130 and 10451008901004542) and the Fundamental Research Funds for the Central Universities (no. 10ykpy19). Disclosure of Interest: None Declared